Reconstruction of Standard Agreement Ethics in Bank Credit Agreements: Integration of Human Rights and Local Wisdom of Bali (Contrarius Series: Law & Social Justice, 2026)
Standard agreements in the banking world often create an imbalance in the position between banks and customers, thereby potentially ignoring the values of justice and humanity. This research aims to analyze the application of standard agreements in bank credit agreements from a Human Rights (HAM) perspective, a s well as offering a reconstruction of the ethics of standard agreements by integrating local Balinese wisdom values. The method used is a juridical-normative approach with a conceptual and reflective character. The results of the study show that standard agreement practices that are too rigid can lead to violations of hu man rights principles, especially the right to equality and justice in contracts. Balinese local wisdom value s such as Tri Hita Karana, Tat Twam Asi, Segilik- Seguluk, and Paras-Paros Sarpanaya can be the basis for reconstructing banking ethics that are humanist, inclusive, and socially just.